The calcium transient coupled to the L-type calcium current attenuates cardiac alternans - Warren, Mark; Poelzing, Steven (Frontiers in Physiology, 2024)
Cardiac action potential (AP) alternans have been linked to the development of arrhythmia. AP alternans may be driven by AP instabilities, Ca2+ transient (CaT) instabilities, or both. The mechanisms underlying CaT driven AP alternans is well-supported experimentally, but the ionic mechanism underlying alternans driven by AP instabilities remain incompletely understood. Here we used the Ca2+ buffer BAPTA to remove the CaT and generate a model of AP alternans driven primarily by AP instabilities. In isolated rabbit ventricle myocytes, AP alternans induced by rapid pacing were either critically damped and persisted over time, overdamped and ceased over seconds, or underdamped progressing to 2:1 capture. Control cells predominantly exhibited critically damped alternans. In contrast, removing CaT with BAPTA destabilized alternans formation in a concentration dependent manner. Importantly, alternans were easier to induce in CaT free cells as evidenced by a higher alternans threshold relative to control cells. While the L-type Ca2+ channel agonist Bay K 8644 had a minor effect on alternans formation in myocytes with conserved CaT, combining the agonist with BAPTA markedly promoted the formation of underdamped alternans and increased the alternans threshold more than four-fold as compared to controls. Our data support a mechanistic model in which AP alternans are a primary self-sustained event in which the CaT serves as a dampening cue that curbs alternans development, likely via a canonical negative feedback process involving Ca2+ induced inhibition of L-type calcium current.